Partisipasi Politik Pemilih Muda Dalam Pilkada Ditengah Pusaran Korupsi Kepala Daerah: (Studi pada Pilkada Provinsi Lampung Tahun 2024) - Bendi, Bendi Juantara (Jurnal Kajian Pemerintah: Journal of Government, Social and Politics, 2024)
The high number of corruption cases of regional heads in Lampung Province has threatened a crisis in the integrity of regional leadership. Based on the results of secondary data observations, it shows that regional heads in various regions in Lampung Province are caught in the KPK's OTT. Even though relevant stakeholders have made various preventive efforts to reduce the prevalence of corrupt practices, there are still problems and obstacles in law enforcement and abuse of authority. The general objectives of this research are; first, to see the extent to which massive regional head corruption practices occur in Lampung Province, second, the potential of young voters in the 2024 regional head election contestation in Lampung Province, third, the challenges of young voters in political participation amidst the maelstrom of regional head corruption. Researchers used a qualitative descriptive approach with data collection techniques through documents and literature study analysis. The research results show that after the implementation of the direct regional head election regulations in Lampung Province, 8 regional heads were involved in corruption cases. Corruption cases that hold regional heads hostage are a dilemma for young voters in determining their choice in the 2024 regional elections. On the one hand, based on age groups and generations, the large number of young voters (Millennials and Gen-Z) can contribute to the victory of regional heads, but on the other hand, voters' political participation It is doubtful that young people will be able to achieve their maximum due to the vortex of corruption holding regional heads hostage.